Sublethal and transgenerational effects of a potential plant‐derived insecticide, β‐asarone, on population fitness of brown planthopper, Nilaparvata lugens. Issue 7 (27th May 2022) - Xu, Xueliang; Li, Xiang; Wen, Dong; Zhao, Chenchen; Fan, Linjuan; Wu, Caiyun; Liu, Zirong; Han, Kehong; Zhao, Muhua; Zhang, Shu; Yao, Yingjuan
Abstract: Many essential oils have excellent insecticidal activity and have the potential to be developed as alternatives to chemical insecticides for pest control. Previously, we showed that β‐asarone, a major constituent of the essential oil derived from Acorus calamus L. (Acoraceae), has strong pesticidal activity against brown planthopper, Nilaparvata lugens (Stål) (Hemiptera: Delphacidae), the most notorious rice pest in Asia. Here, we report the first evaluation of the sublethal and transgenerational effects of β‐asarone on N. lugens . β‐Asarone significantly decreased female longevity, male longevity, fecundity, and hatchability of F0 generation individuals exposed to the LD30 and LD45 of β‐asarone relative to the acetone control. Moreover, compared with acetone, exposure to LD30 and LD45 of β‐asarone significantly shortened the duration of the egg stage, developmental duration of first instars, and female longevity of F1 generation individuals. Furthermore, the intrinsic rate of increase (r), finite rate of increase (λ), and net reproductive rates (R0 ) of insects treated with LD30 and LD45 of β‐asarone were significantly lower than those of insects treated with acetone. Compared with acetone, the fecundity and hatchability of F1 generation individuals were significantly decreased after exposure to β‐asarone at LD30 and LD45 . These findings indicate the negative effects of sublethal doses of β‐asarone on N. lugens and provide novel information on the potential use of β‐asarone as a substitute chemical pesticide. Abstract : β‐Asarone is the main insecticidal active constituent of essential oil of Acorus calamus (Acoraceae). We systematically evaluated the sublethal and transgenerational effects of β‐asarone on the rice pest Nilaparvata lugens (Hemiptera: Delphacidae). We found significant negative effects of sublethal doses of β‐asarone on the adult longevity, reproductive capacity, and hatchability of N. lugens . Therefore, we conclude that β‐asarone has the potential to become a new compound to replace chemical pesticides to control this notorious pest.